If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(2/3)*y+13 = (4/7)*y // - (4/7)*y
(2/3)*y-((4/7)*y)+13 = 0
(2/3)*y+(-4/7)*y+13 = 0
(2/3-4/7)*y+13 = 0 // - 13
(2/3-4/7)*y = -13 // : 2/3-4/7
y = -13/(2/3-4/7)
y = -13/(2/3-4/7)
| B(b)-7b+12=0 | | (8y+4)(5y+10)=0 | | 2y^2-48=0 | | 2(6a-b)-7(3b-7a)= | | p+2+3p=98 | | 5-(5-33w)=44w-5 | | -3/5x+1/5y=9/5 | | a+7=32 | | 430+5x=1200 | | 9y-6+8=42 | | x3=0.7 | | 18/f=15/11 | | 3x(x-3)=4x+56 | | E/9=91/117 | | 21/12=d/20 | | 10p^2-11p-6= | | 5x+2x^2=-4 | | 21-11/12+17-5/12= | | x+71/2=20 | | 3/8x+1/2y=-3 | | 64x+2=25x+1225 | | x+-4=-3 | | 1/8*2/8 | | 45.1=15t+.5t^2 | | 5+7x=x-19 | | 12k^8/6k^5 | | 45.1=15t | | 7.2-4x=3x+35.2 | | 13x-5=x-19 | | 15t+.5t^2= | | in(x-2)+in(2x+-3)=2inx | | 3x-10=-6x+35 |